Contrasting composition of terrigenous organic matter in the dissolved, particulate and sedimentary organic carbon pools on the outer East Siberian Arctic Shelf; Biogeosciences; Vol. 13, iss. 22 - Salvado J. A. Joan; Tesi T. Tommaso; Sundbom M. Marcus; Karlsson E. S. Emma; Krusa M. E. Martin Elmquist; Semiletov I. P. Igor Petrovich; Panova E. V. Elena Vladimirovna; Gustafsson O. Orjan (2016, 2016)
Title screen